Ondansetron Does Not Reduce Withdrawal in Patients With Physical Dependence on Chronic Opioid Therapy. Issue 5 (September 2017) - Chu, Larry F.; Sun, John; Clemenson, Anna; Erlendson, Matthew J.; Rico, Tom; Cornell, Erika; Obasi, Hannah; Sayyid, Zahra N.; Encisco, Ellen M.; Yu, Jeff; Gamble, Jamison G.; Carroll, Ian; et al.
Abstract : Objectives: Individuals taking opioids for an extended period of time may become physically dependent, and will therefore experience opioid withdrawal should they stop taking the medication. Previous work in animal and human models has shown that the serotonin (5-HT3 ) receptor may be implicated in opioid withdrawal. In this study, we investigated if ondansetron, a 5-HT3 -receptor antagonist, could reduce the symptoms of opioid withdrawal after chronic opioid exposure in humans. Methods: In this double-blinded, randomized, crossover study, 33 chronic back pain patients (N = 33) were titrated onto sustained-release oral morphine for 30 days. After titration, participants attended 2 study sessions, 1 week apart, in which opioid withdrawal was induced with intravenous naloxone, with or without 8 mg intravenous ondansetron pretreatment. Opioid withdrawal symptoms were assessed by a blinded research assistant (objective opioid withdrawal score [OOWS]) and by the research participant (subjective opioid withdrawal score [SOWS]). Results: Clinically significant signs of withdrawal were observed during both the ondansetron (ΔOOWS = 3.58 ± 2.22, P  < 0.0001; ΔSOWS = 12.48 ± 11.18, P  < 0.0001) and placebo sessions (ΔOOWS = 3.55 ± 2.39, P  < 0.0001; ΔSOWS = 12.21 ± 10.72, P  < 0.0001), but no significant differences were seen between the treatment sessions in either the OOWS or SOWS scores. Conclusion: We hypothesized that ondansetron would reduce opioid withdrawal symptoms in human subjects, but found no difference in withdrawal severity between ondansetron and placebo sessions. These findings suggest that more investigation may be necessary to determine if 5-HT3 -receptor antagonists are suitable treatment options for opioid withdrawal.